Assessment of Patients Knowledge about Gastritis at General Kirkuk Hospital in Kirkuk City - Qasim Hussein Mohammed (College of Nursing,University of Mosul, 2015)
Background and aim: Gastritis (inflammation of the gastric or stomach mucosa) is a common GI problem. Gastritis may be acute, lasting several hours to a few days, or chronic, resulting from repeated exposure to irritating agents or recurring episodes of acute gastritis). The aim of the study to assessment of patient Knowledge regarding gastritis at General Kirkuk Hospital in Kirkuk city. Materials and method: descriptive study was carried out on gastritis patients at General Kirkuk hospital in Kirkuk city from the beginning from (10th of June 2013 to5th May 2014) in order to assess knowledge concerning gastritis ,non- probability sampling convenience sample of (50) patients .The data was collected through the application of constructed questionnaire with consist of three parts and were used (SPSS). The Data were analyzed by using descriptive and inferential statistical the frequencies (F), percentage (%), and mean of score. Results : (74%) of the samples (35>) years old, (76%) of them were male, (54%) of the samples were illiterate, (62%) of them were house wife, (88%) of the samples were married, 40%) of them were (4-6) Working hour per day , 32%) of them have history of hypertension,(72%) of the sample had no family history of gastritis, (66%) of them no smoker, (78%) of them had continuous stress. Conclusion: type of the patients gender the highest age that having gastritis is (female), almost highest rate of the sample revealed illiterate of the patient. Majority of the sample show housewife occupational of patient. Almost majority of the sample showed that most of patient was married, The highest rate of patient who having gastritis was complain from chronic disease. The majority of samples were having continuous stress, The highest rate of patient was having good knowledge about medical treatment instruct the people about avoiding taking any medication without physician order. Recommendation: Advice the people to take healthy diet and avoid irritant food, and decrease stress. Keywords: Assessment, Knowledge, Gastritis.